The role of stress in relapse of schizophrenia - Ivezić, Slađana (Psihološka obzorja (Ljubljana), 1995)
The roles of stress in relapse of schizophrenia has not been fully explained yet. In this work stress has been defined as an outside event which is specific in itself and does now depend on the individual's action. We studied individual reactions of schizophrenic patients in the period of aim-alarms in Zagreb. The sample comprised 40 female patients , diagnosed as having schizophrenia (DSMIII R). 20 of them were treated for relapse as in- patients, and the other 20 out-patients showed no signs of relapse in that period. The patients were compared in regard to their clinical picture, courseof disease, defense mechanisms, anxiety tolerance, psychosomatic symptoms and social functioning. Analysis of the results shows that there wereno significant differences clinical picture, course of disease and defense mechanisms. Psychosomatic symptoms and anxiety tolerance prevailed in the group of out-patients in whom we also found an increase in social functioning as compared to the period before air-alarms. The conclusion of theresearch is that a schizophrenic patient's reaction to stress depends on the strenght of his ego. Possible reactions are: relapse of the disease, psychosomatic symptoms, anxiety without psychotic breakdown and the usage of negation and omnipotence.
Keywords: psihopatologija; duševni bolniki; stres; shizofrenija